Silicon-carbon negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery
By using silicon-carbon anode material in the negative electrode material of lithium-ion batteries, combining the core layer structure and pore buffer of the carbon skeleton and silicon material, the structural collapse problem caused by volume expansion during charging and discharging of silicon materials is solved, and high cycling performance and the first Coulomb efficiency improvement are achieved.
Patent Information
- Application Number
- CN202411723774.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-28
AI Technical Summary
As the negative electrode material of lithium-ion batteries, silicon has low conductivity and collapses due to volume expansion during charging and discharging, resulting in poor cycle life and low Coulomb efficiency for the first time.
Silicon-carbon negative electrode material is used, and its core layer includes a carbon skeleton and a silicon material. A pore structure is constructed through the template method to buffer the expansion of the silicon material, and an external carbon cladding layer is added to reduce the specific surface area and control the ratio of the pore volume to the silicon element and carbon element.
It improves the circulation performance of silicon-carbon anode material and the first Coulomb efficiency, extends the cycle life of the battery, and takes into account high capacity and high rate performance.
Smart Images

Figure CN119601624A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for lithium-ion batteries, and in particular to a silicon-carbon negative electrode material and a preparation method thereof, a negative electrode sheet and a lithium-ion battery. Background Art
[0002] With the development of the new energy industry, people have put forward more and more stringent requirements on the energy density of lithium batteries. The capacity development of traditional lithium-ion negative electrode material graphite has approached its theoretical capacity, and it is urgent to develop new negative electrode materials to meet the demand for high energy density. Silicon negative electrode materials have ultra-high theoretical capacity, and they also have the advantages of wide sources and low toxicity. They are the most promising next-generation lithium-ion battery negative electrode materials.
[0003] However, as an intrinsic semiconductor, silicon has extremely low electrical conductivity. In addition, during the insertion and extraction of lithium ions, the huge volume expansion of silicon will lead to the fragmentation of active materials, the continuous rupture and repair of solid electrolyte membranes, and the peeling of current collector layers, which will bring problems such as poor cycle performance and low initial coulombic efficiency to silicon-based batteries, thus curbing their large-scale development.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The first object of the present invention is to provide a silicon-carbon negative electrode material, wherein the core layer includes a carbon skeleton and a silicon material, wherein the silicon material can provide a higher gram capacity, the carbon skeleton can provide a certain mechanical strength and enhance the conductivity of the material, and the core layer has a porous structure, which can provide a buffer space when the silicon material is charged, reduce internal stress, prevent material pulverization, and improve cycle performance; the shell carbon coating layer outside the core layer can effectively reduce the specific surface area of the material, avoid direct contact between the silicon material and the electrolyte, and improve the first coulomb efficiency; the silicon-carbon negative electrode material satisfies the relationship 0.5≤S 孔 / (S 硅 +S 碳 )≤2, which can ensure that the silicon material has sufficient buffer space, which is conducive to further improving the cycle performance and taking into account both the capacity and the first coulomb efficiency. It solves the problem of low conductivity of silicon itself and the collapse of the structure caused by volume expansion during the charge and discharge process, resulting in poor cycle life and low first coulomb efficiency.
[0006] The second purpose of the present invention is to provide a method for preparing a silicon-carbon negative electrode material. A large number of pores are constructed inside the material by a template method, which can provide an effective buffer space for the expansion of the silicon material during the charging process and improve the material pulverization problem caused by the silicon material cycle process; at the same time, a carbon layer is provided to coat the porous carbon silicon, which can effectively reduce the specific surface area of the material, reduce the occurrence of side reactions in contact with the electrolyte, and improve the first coulombic efficiency of the silicon-carbon negative electrode material.
[0007] The third object of the present invention is to provide a negative electrode sheet having a long cycle life, high capacity, high first coulombic efficiency and good rate performance.
[0008] The fourth object of the present invention is to provide a lithium ion battery having excellent electrochemistry, good cycle performance, high gram capacity and first coulombic efficiency, good rate performance and the like.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] The present invention first provides a silicon-carbon negative electrode material, the silicon-carbon negative electrode material comprises a composite fiber, the composite fiber comprises a core layer and a carbon coating layer coated on the outer surface of the core layer; wherein the core layer has a pore structure, and the core layer comprises a carbon skeleton and a silicon material dispersed in the carbon skeleton; in the cross section of the composite fiber, the area of the pore structure is S 孔 , the area of silicon element is S 硅 , the area of carbon element is S 碳 , then 0.5≤S 孔 / (S 硅 +S 碳 )≤2.
[0011] Furthermore, the average diameter of the composite fiber is 0.5-3 μm.
[0012] Furthermore, the average length of the composite fiber is 0.8-10 μm.
[0013] Furthermore, the ratio of the average diameter to the average length of the composite fiber is 0.2 to 0.7.
[0014] Furthermore, the average diameter of the core layer in the composite fiber is 0.3-2.5 μm.
[0015] Furthermore, the average diameter of the core layer accounts for 50% to 95% of the average diameter of the composite fiber.
[0016] Furthermore, the specific surface area of the silicon-carbon negative electrode material is 40 to 50 m 2 / g.
[0017] Furthermore, the average pore diameter of the pore structure is 50-100 nm.
[0018] Furthermore, a scanning electron microscope is used in conjunction with an energy spectrometer to obtain the S 孔 The S was obtained by cross-sectional SEM testing and in-situ EDS testing. 硅 and the S 碳 .
[0019] The present invention further provides a method for preparing the silicon-carbon negative electrode material, comprising the following steps: mixing a carbon source, a silicon source, a pore-forming agent and a solvent to obtain a core layer spinning solution; mixing a carbon source and a solvent to obtain a shell layer spinning solution; coaxially electrospinning the core layer spinning solution and the shell layer spinning solution and then drying them to obtain a precursor material with a core-shell structure; carbonizing the precursor material to obtain a silicon-carbon composite fiber material; mixing the silicon-carbon composite fiber material with an etching solution and etching them to obtain the silicon-carbon negative electrode material.
[0020] Furthermore, the carbon sources in the core layer spinning solution and the shell layer spinning solution are each independently selected from at least one of polyacrylonitrile, polyvinyl pyrrolidone, polyethylene imine, polyacrylamide, polyethylene glycol, polyethylene oxide, polylactic acid, polycaprolactone, polyglycolic acid, polyhydroxyalkanoate, polybutylene succinate, cellulose, cellulose acetate, ethyl cellulose, hydroxypropyl methylcellulose, chitin, chitosan, collagen, gelatin, lecithin, silk protein, zein and wheat protein.
[0021] Furthermore, the silicon source includes Si, SiO x , silicon alloy, silane coupling agent, silicone oil, liquid silicone rubber and silicone resin.
[0022] Furthermore, the pore-forming agent includes at least one of zinc oxide, titanium dioxide, copper oxide, iron oxide, cobalt oxide and nickel oxide.
[0023] Furthermore, the median particle size of the pore-forming agent is 20 to 50 nm.
[0024] Further, the solvent includes at least one of CH2Cl2, hexafluoroisopropanol, CHCl3, trifluoroacetic acid, dimethylformamide, dimethylacetamide, tetrahydrofuran, acetone, water, isopropanol, ethanol, methanol and 4-methylmorpholine-N-oxide.
[0025] Furthermore, the mass ratio of the carbon source, the silicon source, the pore-forming agent and the solvent in the core layer spinning solution is 1:0.05-0.1:0.1-0.3:5-30.
[0026] Furthermore, the mass ratio of the carbon source to the solvent in the shell spinning solution is 1:5-30.
[0027] Furthermore, the inner diameter of the inner layer of the coaxial spinning needle used for the coaxial electrospinning is 0.2-1 mm, and the inner diameter of the outer layer is 1.3-1.7 mm.
[0028] Furthermore, the etching solution includes at least one of a hydrochloric acid solution, a sulfuric acid solution, an acetic acid solution and a nitric acid solution.
[0029] Furthermore, the voltage of the coaxial electrospinning is 13-20 kV, and the propulsion rate is 0.01-0.1 mm / min.
[0030] Furthermore, the carbonization temperature is 650-850° C., the heat preservation time is 3-8 hours, and the heating rate is 2-10° C. / min.
[0031] Furthermore, after the carbonization, the silicon-carbon composite fiber material is ball-milled for 5 to 60 minutes.
[0032] Furthermore, the etching time is 12 to 24 hours.
[0033] The present invention further provides a negative electrode sheet, comprising the silicon-carbon negative electrode material.
[0034] The present invention also provides a lithium ion battery, comprising the negative electrode sheet.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) The silicon-carbon negative electrode material provided by the present invention, the core layer of the composite fiber includes a carbon skeleton and a silicon material, wherein the silicon material can provide a higher gram capacity, and the carbon skeleton can provide a certain mechanical strength and enhance the conductivity of the material. At the same time, the core layer has a porous structure, which can provide a buffer space when the silicon material is charged, reduce internal stress, prevent material pulverization, and improve cycle performance. In addition, the carbon coating layer of the composite fiber can effectively reduce the specific surface area of the material, avoid direct contact between the silicon material and the electrolyte, and improve the initial coulomb efficiency. Furthermore, the present invention controls the silicon-carbon negative electrode material to satisfy the relationship 0.5≤S 孔 / (S 硅 +S 碳 )≤2, that is, controlling the ratio of pore volume to silicon and carbon elements, as well as the uniformity of distribution of pores, silicon materials and carbon materials in the composite fibers, can ensure that the silicon material has sufficient expansion buffer space and effectively reduce internal stress, thereby further improving the cycle performance of the silicon-carbon negative electrode material.
[0037] (2) The silicon-carbon negative electrode material provided by the present invention can improve the conductivity of the silicon material, reduce the internal resistance of the battery cell, and thus enhance the rate performance of the battery cell by compounding the silicon material with the carbon material and wrapping the silicon material in a conductive carbon skeleton.
[0038] (3) The silicon-carbon negative electrode material provided by the present invention can effectively shorten the migration path of lithium ions within the material by controlling the ratio of the average diameter to the average length of the composite fibers.
[0039] (4) The preparation method of the silicon-carbon negative electrode material provided by the present invention constructs a large number of pores inside the material through the template method, which can provide an effective buffer space for the expansion of the silicon material during the charging process, and improve the material pulverization problem caused by the silicon material cycle process. At the same time, the carbon layer is provided to cover the porous carbon silicon, which can effectively reduce the specific surface area of the material, reduce the occurrence of side reactions in contact with the electrolyte, and improve the first coulombic efficiency of the silicon-carbon negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0041] Figure 1 This is a schematic diagram of the structure of the silicon-carbon negative electrode material provided by the present invention. DETAILED DESCRIPTION
[0042] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0043] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0044] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0045] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.
[0046] In a first aspect, the present invention provides a silicon-carbon negative electrode material, wherein the silicon-carbon negative electrode material comprises a plurality of composite fibers, wherein the composite fibers are in a linear, strip, or cylindrical shape.
[0047] like Figure 1 The structure diagram of the silicon-carbon negative electrode material is shown. The composite fiber includes a core layer and a carbon coating layer coated on the outer surface of the core layer. That is, the carbon coating layer is the outer layer, or the shell layer.
[0048] Among them, see Figure 1 , the core layer has a pore structure, that is, the core layer has a plurality of pores.
[0049] See also Figure 1 The core layer includes a carbon skeleton and a silicon material uniformly dispersed in the carbon skeleton, that is, the core layer is a composite layer having pores and containing carbon and silicon. It can be understood that the carbon skeleton and the silicon material are uniformly distributed, and the silicon material can also be dispersed on the outer surface of the carbon skeleton.
[0050] On the cross section of the composite fiber, the area of the pore structure is S 孔 , the area of silicon element is S 硅 , the area of carbon element is S 碳 , then S 孔 , S 硅 and S 碳 Satisfies the following relationship: 0.5≤S 孔 / (S 硅 +S 碳 )≤2. Among them, S 孔 / (S 硅 +S 碳 ) includes but is not limited to any point value of 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or any range value between two of them. It can be understood that the area of the carbon element here is the sum of the carbon area in the cross-section core layer and the carbon area in the carbon coating layer.
[0051] That is, the composite fiber is subjected to a cross-sectional SEM test, and the pore cross-sectional area observed under the cross-sectional electron microscope is S 孔 The area of silicon element observed by EDS is S 硅 The area of carbon element observed by EDS is S 碳 Understandably, S孔 , S 硅 and S 碳 The units are the same.
[0052] The silicon-carbon negative electrode material provided by the present invention comprises a core layer of a composite fiber including a carbon skeleton and a silicon material, wherein the silicon material can provide a higher gram capacity, and the carbon skeleton can provide a certain mechanical strength and enhance the conductivity of the material. At the same time, the core layer has a porous structure, which can provide a buffer space when the silicon material is charged, reduce internal stress, prevent material pulverization, and improve cycle performance.
[0053] In addition, the carbon coating of the composite fiber can effectively reduce the specific surface area of the material, avoid direct contact between the silicon material and the electrolyte, and improve the initial Coulomb efficiency.
[0054] Furthermore, the present invention controls the silicon-carbon negative electrode material to satisfy the relationship 0.5≤S 孔 / (S 硅 +S 碳 )≤2, that is, controlling the ratio of pores, silicon elements and carbon elements, as well as the uniformity of the distribution of pores, silicon materials and carbon materials in the composite fibers, can ensure that the silicon material has sufficient buffer space, thereby further improving the cycle performance of the silicon-carbon negative electrode material, while also taking into account the capacity and first coulombic efficiency of the material.
[0055] In addition, the present invention can improve the conductivity of the silicon material and reduce the internal resistance of the battery cell (battery), thereby improving the rate performance of the battery cell (battery) by compounding the silicon material with the carbon material and wrapping the silicon material in a conductive carbon skeleton.
[0056] In some specific embodiments, the average diameter of the composite fiber is 0.5-3 μm, including but not limited to any point value of 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm or a range value between any two of them.
[0057] In some specific embodiments, the average length of the composite fiber is 0.8 to 10 μm, including but not limited to any point value of 0.8 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm, or a range value between any two of them.
[0058] In some specific embodiments, the ratio of the average diameter to the average length of the composite fiber is 0.2 to 0.7, including but not limited to any point value of 0.2, 0.3, 0.4, 0.5, 0.6, 0.65, 0.7 or any range value between two of them. This range can effectively shorten the migration path of lithium ions in the material.
[0059] In some specific embodiments, the average diameter of the core layer in the composite fiber is 0.3-2.5 μm, including but not limited to any point value of 0.3 μm, 0.365 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.6 μm, 0.8 μm, 1 μm, 1.3 μm, 1.5 μm, 1.8 μm, 2 μm, 2.2 μm, 2.5 μm or any range value between two of them. This is conducive to improving the cycle performance, capacity and first coulomb efficiency of silicon-carbon negative electrode materials.
[0060] In some specific embodiments, the average diameter of the core layer accounts for 50% to 95% of the average diameter of the composite fiber, including but not limited to 50%, 51%, 52%, 53%, 55%, 58%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% of any point value or any range value between two of them. This is conducive to improving the cycle performance, capacity and first coulomb efficiency of silicon-carbon negative electrode materials.
[0061] In some specific embodiments, the specific surface area of the silicon-carbon negative electrode material is 40 to 50 m 2 / g, including but not limited to 40m 2 / g, 41m 2 / g, 42m 2 / g, 43m 2 / g, 45m 2 / g, 46m 2 / g, 48m 2 / g, 50m 2 / g or any point value or any range value between the two. A suitable specific surface area can balance the first coulombic efficiency and the electrochemical reaction activity.
[0062] In some specific embodiments, the specific surface area of the silicon-carbon negative electrode material can be controlled by the heating rate and holding time of the carbonization process.
[0063] In some specific embodiments, the average pore size of the pore structure is 50-100 nm, including but not limited to any point value of 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, or any range value between two thereof. This is conducive to providing sufficient expansion buffer space for the silicon material after charging.
[0064] In some specific embodiments, a scanning electron microscope (SEM) is used in conjunction with an energy dispersive spectrometer (EDS) to obtain the SEM cross-sectional image. 孔 The S was obtained by cross-sectional SEM testing and in-situ EDS testing. 硅 and the S 碳 .
[0065] That is, the S 孔 The S is obtained by computer calculation through cross-sectional SEM test. 硅 and the S 碳 The cross-sectional SEM test is combined with the EDS test and is obtained by computer calculation. It is understood that the scanning electron microscope (SEM) can be used in conjunction with the energy dispersive spectrometer (EDS), and the EDS test can be performed in situ after the SEM test is completed.
[0066] In a second aspect, the present invention provides a method for preparing the silicon-carbon negative electrode material, comprising the following steps:
[0067] The carbon source, silicon source, pore-forming agent and solvent are mixed evenly to obtain a core layer spinning solution.
[0068] The carbon source and the solvent are mixed evenly to obtain a shell spinning solution.
[0069] The core layer spinning solution and the shell layer spinning solution are coaxially electrospun. Specifically, the core layer spinning solution is injected into the inner layer of the coaxial spinning needle, that is, the inner layer sprays the core layer spinning solution, and the shell layer spinning solution is injected into the outer layer of the coaxial spinning needle, that is, the outer layer sprays the shell layer spinning solution, and after the spinning is completed, it is dried to obtain a linear precursor material with a core-shell structure. That is, the material formed after the shell layer spinning solution is dried is in the outer layer, and the material formed after the core layer spinning solution is dried is in the inner layer.
[0070] The precursor material is carbonized and cooled to obtain a silicon-carbon composite fiber material.
[0071] The silicon-carbon composite fiber material is mixed with an etching solution and etched, so that the etching solution reacts with the pore-forming agent and / or the material formed after the pore-forming agent is carbonized (for example, metal oxide is decomposed into a metal element at high temperature) to form a pore structure, which is then filtered, washed and dried to obtain the silicon-carbon negative electrode material.
[0072] The preparation method of the silicon-carbon negative electrode material provided by the present invention constructs a carbon-coated porous silicon carbon fiber structure by coaxial electrospinning, and uses a template to etch to construct a large number of pore structures inside the carbon composite fiber. These pore structures can provide more buffer space for the volume expansion of silicon, and timely release the internal stress caused by the volume expansion of silicon to prevent the material from pulverizing. At the same time, the mechanical strength of the material can be further strengthened by carbon coating, ensuring the timely release of the internal stress of the silicon-based material during the charging and discharging process, as well as the mechanical strength of the fiber material, ensuring the integrity of the active material during the charging and discharging process, and improving the cycle life and first coulomb efficiency of the silicon-carbon negative electrode material and the battery prepared therefrom. In addition, the presence of silicon material increases the gram capacity of the silicon-carbon negative electrode material and the battery prepared therefrom.
[0073] In some specific embodiments, the carbon sources in the core layer spinning solution and the shell layer spinning solution are independently selected from at least one of polyacrylonitrile, polyvinyl pyrrolidone, polyethylene imine, polyacrylamide, polyethylene glycol, polyethylene oxide, polylactic acid, polycaprolactone, polyglycolic acid, polyhydroxyalkanoate, polybutylene succinate, cellulose, cellulose acetate, ethyl cellulose, hydroxypropyl methylcellulose, chitin, chitosan, collagen, gelatin, lecithin, silk protein, zein and wheat protein, for example, one, two, three or more thereof are selected.
[0074] In some specific embodiments, the silicon source includes Si (silicon), SiO x At least one of (silicon oxide), silicon alloy, silane coupling agent (organic silicon chemical reagent), silicone oil, liquid silicone rubber and silicone resin, for example, one, two, three or more thereof are selected.
[0075] Among them, silicone oil includes silicone grease, silicone emulsion, silicone surfactant and the like.
[0076] In some specific embodiments, the Si includes nano-silicon with a particle size of 50 to 150 nm.
[0077] In some specific embodiments, the pore-forming agent includes at least one of zinc oxide, titanium dioxide, copper oxide, iron oxide, cobalt oxide and nickel oxide, for example, one, two, three or more thereof.
[0078] In some specific embodiments, the median particle size Dv50 of the pore former is 20 to 50 nm, including but not limited to any point value of 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, and 50 nm, or a range value between any two of them.
[0079] In some specific embodiments, the solvent includes at least one of CH2Cl2 (i.e., dichloromethane), hexafluoroisopropanol, CHCl3 (i.e., chloroform), trifluoroacetic acid, dimethylformamide (i.e., N,N-dimethylformamide), dimethylacetamide (i.e., N,N-dimethylacetamide), tetrahydrofuran, acetone, water, isopropanol, ethanol, methanol and 4-methylmorpholine-N-oxide, for example, one, two, three or more thereof are selected.
[0080] In some specific embodiments, the mass ratio of the carbon source, the silicon source, the pore-forming agent and the solvent in the core layer spinning solution is 1: 0.05-0.1 (for example, 0.06, 0.07, 0.08 or 0.09): 0.1-0.3 (for example, 0.12, 0.15, 0.18, 0.20, 0.23, 0.25 or 0.27): 5-30 (for example, 10, 15, 20 or 25).
[0081] In some specific embodiments, the mass ratio of the carbon source to the solvent in the shell spinning solution is 1:5 to 30, for example, 1:5, 1:10, 1:15, 1:20, 1:25 or 1:30.
[0082] In some specific embodiments, the inner diameter of the inner layer of the coaxial spinning needle used for the coaxial electrospinning is 0.2-1 mm (e.g., 0.21 mm, 0.28 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm or 0.9 mm), and the outer inner diameter is 1.5-1.7 mm (e.g., 1.3 mm, 1.35 mm, 1.4 mm, 1.45 mm, 1.5 mm, 1.53 mm, 1.55 mm, 1.58 mm, 1.60 mm, 1.62 mm, 1.65 mm or 1.68 mm). It is understood that by regulating the outer inner diameter and the inner inner diameter of the coaxial spinning needle, the ratio of the core layer to the carbon coating layer can be controlled.
[0083] In some specific implementations, the etching solution includes at least one of a hydrochloric acid solution, a sulfuric acid solution, an acetic acid solution, and a nitric acid solution.
[0084] In some specific implementations, the molar concentration of the etching solution is 0.5-3 mol / L, for example, 1 mol / L, 1.5 mol / L or 2 mol / L.
[0085] It is understood that the voltage and the propulsion rate can affect the size of the precursor material and the silicon-carbon composite fiber material. In some specific embodiments, the voltage of the coaxial electrospinning is 13 to 20 kV, including but not limited to any point value of 13 kV, 14 kV, 15 kV, 16 kV, 17 kV, 18 kV, 19 kV, 20 kV or any range value between two thereof; the propulsion rate of the coaxial electrospinning is 0.01 to 0.1 mm / min, including but not limited to any point value of 0.01 mm / min, 0.02 mm / min, 0.03 mm / min, 0.04 mm / min, 0.05 mm / min, 0.06 mm / min, 0.07 mm / min, 0.08 mm / min, 0.09 mm / min, 0.1 mm / min or any range value between two thereof.
[0086] In some specific embodiments, the carbonization temperature is 650-850°C, including but not limited to any point value of 650°C, 660°C, 680°C, 700°C, 720°C, 730°C, 750°C, 780°C, 800°C, 830°C, 850°C or a range value between any two of them.
[0087] In some specific embodiments, the carbonization insulation time is 3 to 8 hours, including but not limited to any one of 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, and 8 hours, or a range between any two of them.
[0088] In some specific embodiments, the carbonization heating rate is 2 to 10°C / min, including but not limited to any one of 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, and 10°C / min, or a range between any two of them.
[0089] In some specific embodiments, after the carbonization, the silicon-carbon composite fiber material is ball-milled for 5 to 60 minutes, including but not limited to any one of 5 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, and 60 minutes, or any range between two of them. It is understood that the product obtained after carbonization is a mesh structure, and the long fibers can be separated and broken into fibers of appropriate lengths by ball milling.
[0090] In some specific embodiments, the etching time is 12 to 24 hours, including but not limited to any point value of 12 hours, 13 hours, 15 hours, 18 hours, 20 hours, 22 hours, and 24 hours, or a range value between any two of them.
[0091] In some specific embodiments, the method for preparing the core layer spinning solution includes: first, mixing the carbon source and the solvent by ultrasonication for 10 to 60 minutes, and then stirring for 20 to 48 hours to form a uniform solution, and then slowly adding the silicon source and the pore-forming agent thereto, stirring for 1 to 4 hours and ultrasonically dispersing for 30 to 90 minutes, and cyclically stirring for 1 to 4 hours and ultrasonically dispersing for 30 to 90 minutes for at least three times to obtain a stable core layer spinning solution.
[0092] In some specific embodiments, the method for preparing the shell spinning solution comprises: mixing the carbon source and the solvent by ultrasonication for 10 to 60 minutes, and then stirring for 20 to 48 hours to obtain a stable shell spinning solution.
[0093] In some specific embodiments, during the coaxial electrospinning process, aluminum foil is used as a receiver. After the coaxial electrospinning is completed, the aluminum foil with the precursor material having a core-shell structure is removed and placed in a vacuum drying oven at 50-70°C for 10-18 hours. After that, the electrospinning membrane on the aluminum foil is torn off, which is the precursor material having a core-shell structure. It can be understood that by using a coaxial electrospinning needle, injecting the core layer spinning solution into the inner layer of the needle, and injecting the shell layer spinning solution into the outer layer of the needle, a core-shell structure in which the outer layer covers the inner layer and is linear can be obtained.
[0094] In some specific implementations, the obtained precursor material is placed in a crucible and carbonized in a tube furnace under an inert gas atmosphere.
[0095] In some specific implementations, stirring is performed during the etching process.
[0096] In some specific implementations, the washing and drying steps include: washing with deionized water at least three times, and then drying in a vacuum drying oven at 180-200° C. for 6-12 hours.
[0097] In a third aspect, the present invention provides a negative electrode sheet comprising the silicon-carbon negative electrode material.
[0098] The negative electrode sheet has a long cycle life, high capacity, high first coulombic efficiency and good rate performance.
[0099] Optionally, the negative electrode sheet further includes at least one of a binder and a conductive agent, which is not limited in the present invention.
[0100] In a fourth aspect, the present invention provides a lithium-ion battery, comprising the negative electrode sheet.
[0101] The lithium-ion battery has excellent electrochemistry, good cycle performance, high gram capacity and first coulombic efficiency, and good rate performance.
[0102] Optionally, the lithium-ion battery further includes a positive electrode sheet, a separator and an electrolyte, which is not limited in the present invention.
[0103] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0104] Example 1
[0105] The method for preparing the silicon-carbon negative electrode material provided in this embodiment comprises the following steps:
[0106] (1) Preparation of core layer spinning solution: Take 1g of polyacrylonitrile (carbon source), add it to 10g of N,N-dimethylformamide (solvent) and ultrasonically disperse it for 10 minutes, then stir it for 24 hours to form a uniform solution. Then slowly add 50mg of nano-silicon (silicon source) and 100mg of zinc oxide nanopowder (pore-forming agent, median particle size is 30nm), and repeat stirring for 1h and ultrasonic dispersion for 30min (stirring for 1h and ultrasonic dispersion for 30min, cycle 3 times) to obtain a stable core layer spinning solution. That is, the mass ratio of carbon source, silicon source, pore-forming agent and solvent in the core layer spinning solution is 1:0.05:0.1:10.
[0107] (2) Preparation of shell spinning solution: 0.5 g of polyacrylonitrile (carbon source) was added to 10 g of N,N-dimethylformamide (solvent) for ultrasonic dispersion for 10 min, followed by stirring for 24 h to obtain a stable shell spinning solution. That is, the mass ratio of the carbon source to the solvent in the shell spinning solution was 1:20.
[0108] (3) Coaxial electrospinning: The core layer spinning solution and shell layer spinning solution were added to the core layer and shell layer syringes respectively, and the coaxial spinning needle was connected (the inner diameter of the inner layer of the coaxial spinning needle was 0.21 mm and the inner diameter of the outer layer was 1.3 mm). The aluminum foil was used as the receiver, and the coaxial electrospinning voltage was set to 16 kV and the propulsion rate was set to 0.1 mm / min to perform coaxial electrospinning. After completion, the aluminum foil was removed and placed in a vacuum drying oven at 60°C for 10 h, and then the electrospinning membrane on the aluminum foil was torn off to obtain a precursor material with a core-shell structure.
[0109] (4) Carbonization: The precursor material obtained in step (3) is placed in a crucible, heated to 700°C at a heating rate of 2°C / min in a tubular furnace under an inert gas atmosphere, and then kept warm for 3 hours. After cooling to room temperature, the product is taken out and ball-milled for 10 minutes to obtain a silicon-carbon composite fiber material powder.
[0110] (5) Etching: Take the silicon-carbon composite fiber material powder obtained in step (4) and put it into a 1 mol / L hydrochloric acid solution (etching solution), stir and etch for 12 hours, then filter it, wash it with deionized water three times, and then put it into a vacuum drying oven at 200°C for 6 hours to obtain a silicon-carbon negative electrode material.
[0111] The silicon-carbon negative electrode material prepared in this embodiment includes composite fibers, the average diameter of the composite fibers is 0.83 μm, the average length is 1.28 μm, and the ratio of the average diameter to the average length is 0.65. The composite fibers include a core layer and a carbon coating layer coated on the outer surface of the core layer. The core layer has a pore structure with an average pore size of 32 nm. The core layer includes a carbon skeleton and silicon materials dispersed in the carbon skeleton. The average diameter of the core layer is 0.6 μm, and the average diameter of the core layer accounts for 72.2% of the average diameter of the composite fibers. The composite fibers were subjected to SEM testing, and the area of the pore structure observed under the cross-sectional SEM was S 孔 The area of silicon element observed by EDS is S 硅 The area of carbon element observed by EDS is S 碳 , S 孔 / (S 硅 +S 碳 )=0.5. The specific surface area of the silicon-carbon negative electrode material was tested and its specific surface area was 40m 2 / g.
[0112] Example 2
[0113] The preparation method of the silicon-carbon negative electrode material provided in this embodiment is basically the same as that in Example 1, except that in step (1), the mass of the zinc oxide nanopowder is replaced with 200 mg, that is, the mass ratio of the carbon source, silicon source, pore-forming agent and solvent in the core layer spinning solution is 1:0.05:0.2:10.
[0114] Example 3
[0115] The preparation method of the silicon-carbon negative electrode material provided in this embodiment is basically the same as that in Example 1, except that in step (1), the mass of the zinc oxide nanopowder is replaced with 300 mg, that is, the mass ratio of the carbon source, silicon source, pore-forming agent and solvent in the core layer spinning solution is 1:0.05:0.3:10.
[0116] Example 4
[0117] The preparation method of the silicon-carbon negative electrode material provided in this embodiment is basically the same as that in Example 1, except that in step (1), the mass of nano-silicon is replaced with 100 mg, that is, the mass ratio of the carbon source, silicon source, pore-forming agent and solvent in the core layer spinning solution is 1:0.1:0.1:10.
[0118] Example 5
[0119] The method for preparing the silicon-carbon negative electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that in step (1) and step (2), polyacrylonitrile is replaced by polyethyleneimine of equal mass, respectively.
[0120] Example 6
[0121] The preparation method of the silicon-carbon negative electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that in step (1), the nano-silicon is replaced by a silane coupling agent of an equal mass in terms of silicon element.
[0122] Example 7
[0123] The preparation method of the silicon-carbon negative electrode material provided in this embodiment is basically the same as that in Example 1, except that in step (1), the median particle size of the zinc oxide nanopowder is 50 nm.
[0124] Example 8
[0125] The preparation method of the silicon-carbon negative electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that in step (1), the zinc oxide nanopowder is replaced with an equal mass of copper oxide.
[0126] Example 9
[0127] The preparation method of the silicon-carbon negative electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that, in step (3), the inner diameter of the inner layer of the coaxial spinning needle is 1 mm, and the inner diameter of the outer layer is 1.7 mm.
[0128] Example 10
[0129] The preparation method of the silicon-carbon negative electrode material provided in this embodiment is basically the same as that in Example 1, except that in step (3), the coaxial electrospinning voltage is 20 kV and the propulsion rate is 0.05 mm / min.
[0130] Embodiment 11
[0131] The preparation method of the silicon-carbon negative electrode material provided in this embodiment is basically the same as that in Example 1, except that in step (4), the carbonization parameters are: heating to 800° C. at a heating rate of 5° C. / min and then keeping the temperature for 6 hours.
[0132] Example 12
[0133] The preparation method of the silicon-carbon negative electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that, in step (5), the silicon-carbon composite fiber material powder is placed in a 1 mol / L acetic acid solution and stirred and etched for 15 h.
[0134] Comparative Example 1
[0135] The preparation method of the silicon-carbon negative electrode material provided in this comparative example is basically the same as that in Example 1, except that in step (1), no zinc oxide nanopowder is added.
[0136] Comparative Example 2
[0137] The preparation method of the silicon-carbon negative electrode material provided in this comparative example is basically the same as that in Example 1, except that in step (1), the mass of the zinc oxide nanopowder is replaced with 500 mg, that is, the mass ratio of the carbon source, silicon source, pore-forming agent and solvent in the core layer spinning solution is 1:0.05:0.5:10.
[0138] The indicators of the silicon-carbon negative electrode materials prepared in each embodiment and each comparative example are shown in Table 1. The scanning electron microscope (SEM) and the energy dispersive spectrometer (EDS) were used together to obtain the SEM cross-sectional test results. 孔 , S was obtained by cross-sectional SEM test and in-situ EDS test 硅 and S 碳 .
[0139] Table 1 Physical and chemical indicators of silicon-carbon negative electrode materials prepared in various embodiments and comparative examples
[0140]
[0141]
[0142] Experimental example
[0143] The silicon-carbon negative electrode materials prepared in each embodiment and each comparative example were used as active materials, and were added to the solvent NMP according to the mass ratio of active material: PVDF: conductive agent = 91.6: 6.6: 1.8 to make a slurry, and the slurry was coated on the Cu foil current collector, then dried, and rolled twice with a pressure of 15t. Then it was cut into small discs with a diameter of 16mm by a cutting machine, and dried at 110℃ in vacuum for 1h to obtain a negative electrode sheet. Each negative electrode sheet was assembled into a button cell in sequence with a diaphragm, a lithium sheet, nickel foam and an electrolyte. After being placed at a high temperature of 45℃ for 12h, the electrochemical properties (first effect, cycle, rate and gram capacity test) of each button cell were tested with a blue electric test cabinet, and the results are shown in Table 2.
[0144] Among them, the electrochemical performance test method is as follows:
[0145] First charge and discharge coulomb efficiency test: put the assembled button cell on the test cabinet and clamp it, discharge it to 5mV with 6mA current, get the discharge capacity C1, let it stand for 5min, then charge it to 0.8V with 6mA current, get the charge capacity C2. First charge and discharge efficiency = C1 / C2×100%.
[0146] Cycle 500 cycles capacity retention test: discharge at 6mA to 0.05V, leave for 5min. Then charge at 6mA to 0.05V, leave for 5min, and perform cycle test. The discharge capacity of the second cycle is C3, and the discharge capacity of the nth cycle is C n , capacity retention rate = C n / C3×100%.
[0147] 4C discharge capacity retention rate test: (1) Discharge at 6mA to 0.05V and let it sit for 5min. Then charge at 6mA to 0.05V and let it sit for 5min. Repeat 4 cycles and take the average discharge capacity of the last three cycles as C4mAh. (2) Charge at C4mA to 0.8V and let it sit for 5min. Then discharge at C4mA to 0.05V and let it sit for 5min. The discharge capacity is recorded as AmAh. Then charge at C4mA to 0.8V and let it sit for 5min. Discharge at 4C4mA to 0.05V and let it sit for 5min. The discharge capacity is recorded as BmAh. 4C discharge capacity retention rate = B / A×100%.
[0148] Gram capacity test: weigh the negative electrode material minus the weight of the current collector and record it as m, discharge it at 6mA to 0.05V, and let it sit for 5min. Then charge it at 6mA to 0.05V and let it sit for 5min. Cycle 4 times, and take the average of the last three cycles and record it as C5. Gram capacity = C5 / m.
[0149] Table 2 Electrochemical test results of button cells
[0150]
[0151]
[0152] It can be seen from Table 1 that the silicon-carbon negative electrode material prepared in each embodiment has excellent cycle performance, and has high gram capacity, high first coulombic efficiency and high rate performance.
[0153] However, since Comparative Example 1 does not have a porous structure, the cycle performance is significantly reduced, and the rate performance is also reduced.
[0154] Comparative Example 2 does not satisfy the relationship 0.5≤S 孔 / (S 硅 +S 碳 )≤2, resulting in a significant decrease in the cycle performance and a decrease in the first coulombic efficiency.
[0155] It can be seen that the silicon-carbon negative electrode material provided by the present invention can provide a buffer space for silicon expansion, thereby improving the cycle performance; and the silicon-carbon negative electrode material has high capacity, high first coulombic efficiency and high rate performance.
[0156] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A silicon-carbon negative electrode material, characterized in that: The silicon-carbon negative electrode material comprises a composite fiber, wherein the composite fiber comprises a core layer and a carbon coating layer coated on the outer surface of the core layer; Wherein, the core layer has a porous structure, and the core layer includes a carbon skeleton and silicon material dispersed in the carbon skeleton; In the cross section of the composite fiber, the area of the pore structure is S 孔 , the area of silicon element is S 硅 , the area of carbon element is S 碳 , then 0.5≤S 孔 / (S 硅 +S 碳 )≤2.
2. The silicon-carbon negative electrode material according to claim 1, characterized in that: At least one of the following conditions is met: (1) The average diameter of the composite fiber is 0.5 to 3 μm; (2) The average length of the composite fiber is 0.8 to 10 μm; (3) The ratio of the average diameter to the average length of the composite fiber is 0.2 to 0.
7.
3. The silicon-carbon negative electrode material according to claim 1, characterized in that: The average diameter of the core layer in the composite fiber is 0.3 to 2.5 μm.
4. The silicon-carbon negative electrode material according to claim 1, characterized in that: The average diameter of the core layer accounts for 50% to 95% of the average diameter of the composite fiber.
5. The silicon-carbon negative electrode material according to claim 1, characterized in that: The specific surface area of the silicon-carbon negative electrode material is 40 to 50 m 2 / g.
6. The silicon-carbon negative electrode material according to claim 1, characterized in that: At least one of the following conditions is met: (1) The average pore size of the pore structure is 50 to 100 nm; (2) The SEM was combined with an energy spectrometer to obtain the S 孔 The S was obtained by cross-sectional SEM testing and in-situ EDS testing. 硅 and the S 碳 .
7. The method for preparing the silicon-carbon negative electrode material according to any one of claims 1 to 6, characterized in that: The steps include: A carbon source, a silicon source, a pore-forming agent and a solvent are mixed to obtain a core layer spinning solution; a carbon source and a solvent are mixed to obtain a shell layer spinning solution; the core layer spinning solution and the shell layer spinning solution are coaxially electrospun and then dried to obtain a precursor material with a core-shell structure; Carbonizing the precursor material to obtain a silicon-carbon composite fiber material; The silicon-carbon composite fiber material is mixed with an etching solution and then etched to obtain the silicon-carbon negative electrode material.
8. The method for preparing the silicon-carbon negative electrode material according to claim 7, characterized in that: At least one of the following conditions is met: (1) The carbon sources in the core layer spinning solution and the shell layer spinning solution are independently selected from at least one of polyacrylonitrile, polyvinyl pyrrolidone, polyethylene imine, polyacrylamide, polyethylene glycol, polyethylene oxide, polylactic acid, polycaprolactone, polyglycolic acid, polyhydroxyalkanoate, polybutylene succinate, cellulose, cellulose acetate, ethyl cellulose, hydroxypropyl methylcellulose, chitin, chitosan, collagen, gelatin, lecithin, silk protein, zein and wheat protein; (2) The silicon source includes Si, SiO x , at least one of silicon alloy, silane coupling agent, silicone oil, liquid silicone rubber and silicone resin; (3) the pore-forming agent comprises at least one of zinc oxide, titanium dioxide, copper oxide, iron oxide, cobalt oxide and nickel oxide; (4) The median particle size of the pore-forming agent is 20 to 50 nm; (5) the solvent comprises at least one of CH2Cl2, hexafluoroisopropanol, CHCl3, trifluoroacetic acid, dimethylformamide, dimethylacetamide, tetrahydrofuran, acetone, water, isopropanol, ethanol, methanol and 4-methylmorpholine-N-oxide; (6) The mass ratio of the carbon source, the silicon source, the pore-forming agent and the solvent in the core layer spinning solution is 1:0.05-0.1:0.1-0.3:5-30; (7) The mass ratio of the carbon source to the solvent in the shell spinning solution is 1:5 to 30; (8) The inner diameter of the inner layer of the coaxial spinning needle used for the coaxial electrospinning is 0.2 to 1 mm, and the inner diameter of the outer layer is 1.3 to 1.7 mm; (9) The etching solution includes at least one of hydrochloric acid solution, sulfuric acid solution, acetic acid solution and nitric acid solution; (10) The voltage of the coaxial electrospinning is 13-20 kV, and the propulsion rate is 0.01-0.1 mm / min; (11) The carbonization temperature is 650-850°C, the holding time is 3-8h, and the heating rate is 2-10°C / min; (12) After the carbonization, ball milling the silicon-carbon composite fiber material for 5 to 60 minutes; (13) The etching time is 12 to 24 hours.
9. A negative electrode sheet, characterized in that: It comprises the silicon-carbon negative electrode material as claimed in any one of claims 1 to 6.
10. A lithium ion battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
Silicon-carbon composite material with nano micropores and preparation method as well as application thereof
CN103311523A
Composite anode active material, anode and lithium battery each including the composite anode active material, method of preparing the composite anode active material
CN103682283A
Negative electrode, battery with negative electrode and negative electrode manufacturing method
CN103943821A
Preparation method of composite cathode material of lithium ion battery, composite cathode material of lithium ion battery and lithium ion battery
CN106099073A
Lithium ion battery anode material, and preparation method thereof
CN106571451A
Cited By
Quick-charging lithium battery and preparation method thereof
CN121662734A